Work Overload, Emotional Exhaustion, Emotional Contagion, And Compassion Fatigue In Nurses During COVID-19 Pandemic: A moderated mediation model - Kopuz, Koray; Akman, Eren; Orhan, Seyfullah (Australasian College of Health Service Management, 2024)
Objective: Burnout is stated as a major problem for nurses. The relationship between work overload and burnout, another problem experienced by nurses, has been examined by different authors. However, the effect of mediation and moderation mechanisms that may affect the relationship between work overload and emotional exhaustion in nurses has yet to be clarified to a great extent. This study aims to fill this research gap by examining the mediating role of compassion fatigue and moderating role of emotional contagion in the relationship between work overload and emotional exhaustion. Methods: This descriptive cross-sectional study was conducted in Istanbul, Turkey, with the participation of 330 nurses. The research model was tested with Hayes' PROCESS macro. Results: The result shows that the indirect effect of work overload on emotional exhaustion through compassion fatigue is positive and significant (b = 0.335, 95% confidence intervals (CIs) = (0.243, 0.430)). Also, the indirect effect was found to vary depending on emotional contagion (Index of moderated mediation (IMM) = 0.076, 95% CIs = (0.029, 0.132)). In this context, the effect of work overload on emotional exhaustion through compassion fatigue is stronger in nurses with high emotional contagion levels. Conclusions: The study's findings revealed that emotional contagion and compassion fatigue variables are important mechanisms for clarifying the relationship between work overload and the emotional exhaustion of nurses.
Keywords: Medicine (General); R5-920; Work Overload; Emotional Contagion; Burnout; Nursing; Compassion Fatigue; Public aspects of medicine; RA1-1270